Comprehensive Isolation and Characterization of Theaflavins, Thearubigins and Caffeine as Bioactive Compounds from Darjeeling Black Tea - De, Dwaipee; Deb, Mayukh; Ray, Sonali (Asian Journal of Chemistry, 2024)
The present study aimed to isolate and characterize three major bioactive components viz. theaflavins, thearubigins and caffeine from Darjeeling black tea, which contribute significantly to the cup characteristics and health benefits of black tea. Theaflavins were isolated using Soxhlet extraction followed by column chromatography, HPLC and UV spectroscopy. HPLC showed effective separation of four major theaflavins. Thearubigins were isolated using liquid-liquid extraction and characterized through NMR, FTIR-ATR and UV spectroscopic techniques. The NMR spectral studies suggested thearubigins to be polymeric oxidation products of catechin groups, while FTIR spectral studies indicated similarity with proanthocyanidin-like polymers. Caffeine was isolated via a solid-liquid extraction followed by liquid-liquid extraction and identified using TLC, NMR, UV and SEM techniques. TLC showed an Rf value of 0.65, which is consistent with standard caffeine. The NMR confirmed the purity of isolated caffeine and SEM revealed its needle-shaped crystal morphology. The results show that these bioactive compounds may be efficiently isolated and characterized using chromatographic and spectroscopic methods.